Motion analysis of match play in New Zealand U13 to U15 age-group soccer players - Atan, S. A.; Foskett, A.; Ali, A. (The Journal of Strength and Conditioning Research, 2016)
The purpose of this study was to investigate motion analysis in 85 players (U13-U15 years) from Auckland's Metropolitan League during 2 competitive soccer matches. Five-Hz global positioning system (with interpolated 10-Hz output) units were used to measure total distance (absolute and relative) and time spent in standing, walking, low-intensity running, medium-intensity running, high-intensity running, and sprinting. Speed thresholds for each match activity were determined through mean 10-m flying sprint peak speed for each age group. Under 15 years (U15, 6600 ± 1480 m) covered more absolute distance because of longer playing time than under 14 years (U14, 5385 ± 1296 m, p = 0.001) and under 13 years (U13, 4516 ± 702.6 m, p = 0.001). However, there were no differences in relative distances covered (U15, 94.5 ± 11.2 m/min, U14, 96.1 ± 11.9 m·min-1, U15, 97.3 ± 17.6 m/min, p = 0.685). Maximum speed attained during the match was faster for U15 (26.5 ± 1.68 km/h) than U14 (25.4 ± 1.93 km/h, p = 0.022) and U13 (23.5 ± 1.74 km/h, p = 0.001); there were no differences in average distance per sprint, with all age groups covering ~16 m per sprint (p = 0.603). The current findings provide useful information for developing specific training programs for young soccer players and a framework for developing age-specific soccer simulation protocols.